Pharmacologic Induction of Endotoxin Tolerance in Dendritic Cells by L-Kynurenine - Manni, Giorgia; Mondanelli, Giada; Scalisi, Giulia; Pallotta, Maria Teresa; Nardi, Dario; Padiglioni, Eleonora; Romani, Rita; Talesa, Vincenzo Nicola; Puccetti, Paolo; Fallarino, Francesca; Gargaro, Marco (Frontiers in Immunology, 2020)
Endotoxin tolerance aims at opposing hyperinflammatory responses to lipopolysaccharide (LPS) exposure. The Aryl hydrocarbon Receptor (AhR) participates in protection against LPS-mediated tissue damage, as it plays a necessary role in restraining the proinflammatory action of IL-1 and TNF- while fostering the expression of protective TGF-β. TGF-β, in turn, promotes durable expression of the immune regulatory enzyme indoleamine 2,3-dioxygenase 1 (IDO1). IDO1 degrades L-tryptophan to L-kynurenine – an activating ligand for AhR– thus establishing a feedforward loop. In this study, we further demonstrate that L-kynurenine also promotes the dissociation of the Src kinase–AhR cytosolic complex, leading to the activation of both genomic and non-genomic events in conventional dendritic cells (cDCs) primed with LPS. Specifically, the Src kinase, by phosphorylating the downstream target IDO1, triggers IDO1’s signaling ability, which results in enhanced production of TGF-, an event key to establishing full endotoxin tolerance. We demonstrated that exogenous L-kynurenine can substitute for the effects of continued or repeated LPS exposure and that the AhR–Src–IDO1 axis represents a critical step for the transition from endotoxin susceptibility to tolerance. Moreover, much like fully endotoxin-tolerant DCs (i.e., treated twice with LPS in vitro), DCs – treated once with LPS in vitro and then with kynurenine – confer resistance on naive recipients to an otherwise lethal LPS challenge. This may have clinical implications under conditions in which pharmacologically induced onset of endotoxin tolerance is a therapeutically desirable event.